Study of the Surface Adsorption Properties of Feldspar - Ryszard Dobrowolski; Elzbieta Stefaniak; Bogdan Biliński; Piotr Staszczuk (Adsorption Science & Technology)
The adsorption properties of Polish feldspar towards hydrocarbons from the gaseous phase have been studied and the adsorption energy distribution functions for n-octane, benzene and toluene are presented. It appears that there are three types of adsorption sites present on the feldspar surface examined. Treatment of feldspar with aqua regia led to the elimination of low-energy interaction centres. The adsorption properties of the raw and leached feldspar with respect to Cr VI ions have also been studied. The kinetic curves for the sorption of Cr VI ions exhibited two stages which suggest two different mechanisms of sorption. The adsorption capacity depended on the pH with a maximum for pH = 4.8. The excess adsorption isotherm of Cr VI on the raw feldspar surface showed a maximum value at 20 mmol/dm3 equilibrium concentration of Cr VI ions.